2016
DOI: 10.1177/1069072716679922
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of CAAS Scores in Divergent Social Occupations

Abstract: This research investigated the latent structure and full measurement invariance of the Career Adapt-Abilities Scale (CAAS) in three independent samples of social occupations for the first time, namely, preservice teachers (n ¼ 344), retail workers (n ¼ 394), and mothers (n ¼ 160). Convergent and divergent validity of the CAAS data was tested against scores on the Career Adaptability Scale of the Career Futures Inventory (CA-CFI) using a multitrait-multimethod (MTMM) framework. The criterion validity of the CAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Career adaptability is a psychosocial construct that denotes an individual’s resources for coping with current and anticipated tasks, transitions, and traumas in their occupational roles that, to a large or small degree, alter their social integration (Savickas, 1997). In order to better evaluate career adaptability, an international team of vocational psychologists from 13 countries developed the most widely used Career Adapt-Abilities Scale (CAAS; Mcilveen, Perera, Hoare, & Mclennan, 2018; Savickas & Porfeli, 2012). The CAAS consists of four subscales such as Career Concern, Control, Curiosity, and Confidence.…”
mentioning
confidence: 99%
“…Career adaptability is a psychosocial construct that denotes an individual’s resources for coping with current and anticipated tasks, transitions, and traumas in their occupational roles that, to a large or small degree, alter their social integration (Savickas, 1997). In order to better evaluate career adaptability, an international team of vocational psychologists from 13 countries developed the most widely used Career Adapt-Abilities Scale (CAAS; Mcilveen, Perera, Hoare, & Mclennan, 2018; Savickas & Porfeli, 2012). The CAAS consists of four subscales such as Career Concern, Control, Curiosity, and Confidence.…”
mentioning
confidence: 99%
“…In line with the Social Cognitive Career Theory (Lent et al, 1994 ), during Time 3 and Time 4, teachers in the experimental group may have experienced more meaningful episodes of success related to their teaching practices (e.g., implementing new teaching techniques and classroom management strategies) than those in the control group, as they were offered positive emotional experiences—an important strategy for motivating teachers to apply the lessons learned from the intervention to their unique teaching contexts (Gaines et al, 2019 ). These recurring episodes of success or positive teaching experiences may have then boosted their teaching self-efficacy beliefs to positively influence their performance and work engagement at Time 4 (Brown et al, 2008 ; Mcllveen et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, these resources aim at instilling a sense of personal control in teachers to enable them to aptly manage complex classroom situations, implement novel teaching strategies, and experience greater self-fulfillment and job satisfaction (Wang et al, 2015 ). Research by Mcllveen et al ( 2016 ) has demonstrated that career adaptability is strongly related to teachers’ self-efficacy for instructional strategies, classroom management, and student engagement (the three dimensions of teachers’ sense of self-efficacy explained in the following paragraph). They assert that both career adaptability and teachers’ sense of self-efficacy collectively affect teachers’ work engagement.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Items included: making decisions for myself, taking responsibility for my actions, looking for opportunities to grow as a person, investigating options before making a choice, and observing different ways to do things. The full version has shown reliability estimates within the acceptable to excellent range and has shown initial evidence of construct validity as well as convergent validity with the Career Futures Inventory (McIlveen et al., 2018; Savickas & Porfelli, 2012). Additionally, the CAAS‐SF has demonstrated reliability between 0.75 and 0.92 across different countries and is strongly correlated with the full CAAS (Maggiori et al., 2017).…”
Section: Methodsmentioning
confidence: 99%